A review of learning strategies towards learning outcome - Jamaluddin, Nor Sa’adah; Abd. Kadir, Suhaida; Alias, Siti Noormi; Abdullah, Arnida (2021)
Education is the backbone of a country and it contributes towards economic development by enhancing individual’s market value. Therefore, learners’ achievement in learning and the factor influencing it such as application of learning strategies must be focused on in order to develop high market value among learners. The focus of this study is to review learning strategies that influence learning outcomes. This paper explores the meaning of learning strategies by various researchers. At the same time, it also explores the relationship between dimensions of learning strategies towards learning outcomes and the dimensions are believed to be capable of affecting academic performance. It is concluded that suitable and good learning strategies can lead towards successfulness in learning and academic performance. The findings of previous researchers are also included to support the arguments used in this study.